Relationship Between Flexible Organizational Culture and Innovation Capabilities: The Moderating Effect of Rigid Organizational Culture - RamÃrez, Marco Alberto Núñez; Rivero, Roger Alejandro Banegas; Beltrán, Altayra Geraldine Ozuna; Ãlvarez, Rosalva Irma Castro; RamÃrez, Valeria Carolina León (International Review of Management and Marketing, 2017)
The aim of this research is to evaluate the moderating effect of rigid organizational culture on the relationship between flexible organizational culture and innovation capabilities. As empirical evidence, a sample of 103 companies from Northwest Mexico was obtained through quantitative, correlational and cross-sectional research, with a non-experimental design. Also, Pearson's correlation and stepwise regression were used to test the hypotheses of the study, which were partially proved. It was found that rigid and flexible cultures are complemented to foster the development of innovation capacities. Keywords: organizational culture, innovation capabilities, relation, moderation. JEL Classifications: M140, M3